2023
DOI: 10.1126/scisignal.ade2438
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibition in the mouse spinal cord enhances opioid signaling by suppressing an AMPK-mediated negative feedback loop

Abstract: Opioids and other agonists of the μ-opioid receptor are effective at managing acute pain, but their chronic use can lead to tolerance that limits their efficacy. We previously reported that inhibiting the chaperone protein HSP90 in the spinal cords of mice promotes the antinociceptive effects of opioids in a manner that involved increased activation of the kinase ERK. Here, we found that the underlying mechanism involves the relief of a negative feedback loop mediated by the kinase AMPK. Intrathecal treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous research have shown how regulating and integrating pain information has a purpose. Spinal dorsal horn damage brought on by in ammation and tissue damage following viral infection [9]. The increased autophagy of spinal cord-related nerves may be connected to the maintenance mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research have shown how regulating and integrating pain information has a purpose. Spinal dorsal horn damage brought on by in ammation and tissue damage following viral infection [9]. The increased autophagy of spinal cord-related nerves may be connected to the maintenance mechanism.…”
Section: Introductionmentioning
confidence: 99%